An estimated fiscal Taylor rule for the postwar United States - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2011)
This paper documents the systematic response of postwar U.S. fiscal policy to fiscal imbalances and the business cycle using a multivariate Fiscal Taylor Rule. Adjustments to taxes and purchases both account for a large portion of the fiscal response to debt, while authorities seem reluctant to adjust transfers. As expected, taxes are highly procyclical; purchases are acyclical; and transfers are countercyclical. Neither pattern has changed much over time, except that adjustment happens more slowly after 1981 than before 1980. The role of adjustments to purchases in stabilizing the debt indicates that the recent discussion about spending reversals is highly relevant.
Keywords: E62; E63; H20; H62; 330; Spending reversals; Fiscal Taylor Rule; deficits; fiscal policy; taxes; spending; transfer payments; Finanzpolitik; Taylor-Regel; Konjunktur; Schätzung; USA